2014
DOI: 10.3892/etm.2014.2124
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin protects lipopolysaccharide-induced renal mesangial cells from autophagy

Abstract: The aim of this study was to investigate the effects of erythropoietin (EPO) on the impairment of autophagy induced by lipopolysaccharide (LPS) in primary cultured rat glomerular mesangial cells (GMCs). Rat GMCs were isolated and cultured in normal glucose, high-glucose, LPS or LPS + EPO medium. At 24 and 72 h of culture, the cells were examined for expression levels of the autophagy markers LC3 and p62/sequestosome-1 (SQSTM1) using western blot analysis. At 24 h, no significant difference in the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, the type of renal intrinsic cells involved in the alteration of autophagy as well as the alterations that occur in the autophagic pathway must be further investigated for autophagy-based intervention strategies in the future. Some studies on mesangial cells not only showed that high glucose induced the accumulation of p62, but also showed a reduction in autophagy-related gene expression of patients with DKD, suggesting that autophagic activity was inhibited in mesangial cells in DKD 34,35 . In addition, our previous study showed that the autophagic activity was severely inhibited, and increased expression of LC3 and the accumulation of p62 were found in the renal tubular epithelial cells in DKD 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the type of renal intrinsic cells involved in the alteration of autophagy as well as the alterations that occur in the autophagic pathway must be further investigated for autophagy-based intervention strategies in the future. Some studies on mesangial cells not only showed that high glucose induced the accumulation of p62, but also showed a reduction in autophagy-related gene expression of patients with DKD, suggesting that autophagic activity was inhibited in mesangial cells in DKD 34,35 . In addition, our previous study showed that the autophagic activity was severely inhibited, and increased expression of LC3 and the accumulation of p62 were found in the renal tubular epithelial cells in DKD 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence that EPO/EpoR signaling protects tissue against ischemia and hypoxia through suppression of apoptosis (34), there is limited, and in fact controversial, information about the effect of EPO/EpoR signaling on autophagy (5,6,41,57,95). In an experimental model of neonatal necrotizing enterocolitis, EPO reduced both excessive autophagy and apoptosis (95), suppressed hyperoxia-induced autophagy, and contained cell damage (5).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of excess autophagy could alleviate both acute cardiac injury and promote survival of recipient rats in a LPS-induced cardiomyocyte contractile dysfunction model [9]. Moreover, a study by Bi et al [10] reported that induction of autophagy promoted death of rat renal glomerular mesangial cells, while in hepatocytes, pretreatment with wortmannin could alleviate lipopolysaccharide/D-galactosamine-induced acute hepatocytotoxity and reduce apoptosis and necrosis through inhibition of autophagy [11]. These results indicate that induction of excessive autophagy may be harmful and could aggravate injury to organs.…”
Section: Introductionmentioning
confidence: 99%